Substantive and conceptual issues in tourism research: A personal engagement with Southeast Asia - Victor T. King (2018)
© Penerbit Universiti Sains Malaysia, 2015. The field of tourism studies has generated the same kinds of issues and problems as other multidisciplinary fields of study including area studies. This paper reflects on the progress of tourism research in Southeast Asia from the early 1990s when the field began to gain some momentum. These reflections help chart the ways in which research develops and the reasons that it takes the pathways that it does. Many of the issues which have been addressed recently in debates in area studies, especially with regard to the definition of and rationale for Southeast Asian Studies are also evident in tourism studies and it is worthwhile to compare different multidisciplinary endeavours. The main concerns relate to the definition and rationale of a field of studies in a globalising post-modern world, as well as concerns about methodology, concepts and theories. These issues also require critical observations on recent attempts to move the agenda of tourism research forward, in particular in relation to the sociology of "mobilities." Instead, the concept of "encounter" is reintroduced as a productive way to think about and analyse tourism activities.